Hägnstorlekens betydelse för fårs aktivitet och uppvisande av positiva beteenden - Bergman Karlsson, Isabelle (2018)
Animals who live in captivity has a limited area to live on which can affect their life quality and natural social behaviors. Animals at a zoo meet a lot of known and unknown humans every day, and that can be both positive and negative for the animals. Sheep has a complex social structure and their social behaviors can vary a lot depending on the composition of the group. In the wild ewes live in family groups with their offspring, and the rams live in bachelor groups from when they are sexually mature. Sheep do not have a direct hierarchy, instead it is the strong sense of cohesion of the herd that keeps them together. Usually it is an older ewe who chooses places to eat or rest, and her offspring follows her. Play behavior is an indicator of absence of poor welfare and play is one behavior that is self rewarding for animals which gives them a positive feeling. Among sheep and especially lambs playful social behaviors consist of head-bumping, touch and mounting. Previous studies on calves and heifers has shown an increase in activity and play behaviors when released in a larger enclosure. Other studies’ results have suggested that animals show anticipation behaviors when a positive event is about to happen.